Whole-body diffusion-weighted magnetic resonance imaging for the detection of bone metastases and their prognostic impact in metastatic renal cell carcinoma patients treated with angiogenesis inhibitors. (2nd July 2020) - Beuselinck, Benoit; Pans, Steven; Bielen, Jurgen; De Wever, Liesbeth; Noppe, Nathalie; Vanderschueren, Geert; De Keyzer, Frederik; Baldewijns, Marcella; Lerut, Evelyne; Laenen, Annouschka; Verbiest, Annelies; Roussel, Eduard; et al.
Abstract: Background: Metastatic renal cell carcinoma (mRCC) patients with bone metastases (BM) are at high risk for skeletal related events and have a poorer outcome when treated with vascular endothelial growth factor receptor-tyrosine kinase inhibitors (VEGFR-TKIs). Computed tomography (CT) lacks sensitivity to detect BM in mRCC. We aimed to determine the added value of whole body diffusion-weighted magnetic resonance imaging (WB-DWI/MRI) to CT for the detection of BM in mRCC and to estimate the prognostic impact of the number of BM in mRCC patients treated with VEGFR-TKIs. Material and methods: We conducted a prospective study including consecutive mRCC patients treated with a first-line VEGFR-TKI in the metastatic setting. All patients underwent a pretreatment thoracic-abdominal-pelvic CT and WB-DWI/MRI. CT and WB-DWI/MRI were compared for the detection of BM. The number of detected BM was correlated with response rate (RR), progression-free survival (PFS) and overall survival (OS) after start of the VEGFR-TKI. Results: Ninety-two patients were included. BM were found in 55% of the patients by WB-DWI/MRI and in 43% of the patients by CT ( p = .003). Mean number of BM discovered per patient was 6.8 by WB-DWI/MRI versus 1.9 by CT ( p = .006). The cutoff of ≤5 versus >5 BM on WB-DWI/MRI had the highest discriminative power for all outcome measures. Patients with >5 BM had a lower RR (10% versus 42%), more frequently early progressive disease (43% versus 13%, p = .003), shorter PFS (4 versus 10 months, p = .006) and shorter OS (10 versus 35 months, p < .0001) compared to patients with ≤5 BM. Conclusion: WB-DWI/MRI detects significantly more BM in mRCC patients than CT, allowing better estimation of the prognostic impact of BM in mRCC patients treated with VEGFR-TKIs. The prognostic impact should now be validated in patients treated with immune checkpoint inhibitors.